Role of N-Arachidonoyl-Serotonin (AA-5-HT) in Sleep-Wake Cycle Architecture, Sleep Homeostasis, and Neurotransmitters Regulation - Murillo-Rodríguez, Eric; Di Marzo, Vincenzo; Machado, Sergio; Rocha, Nuno B.; Veras, André B.; Neto, Geraldo A. M.; Budde, Henning; Arias-Carrión, Oscar; Arankowsky-Sandoval, Gloria (Frontiers in Molecular Neuroscience, 2017)
The discovery of the endocannabinoid system, which comprises several molecular entities such as endogenous ligands (the most studied endocannabinoids are N-arachidonoylethanolamine named anandamide (AEA) and 2-arachidonoylglycerol (2-AG)), receptors (CB1 and CB2). The endocannabinoid system includes enzymes that synthesize AEA and 2-AG as well as the inactivating enzymes (fatty acid amide hydrolase (FAAH) for AEA and monoacylglycerol lipase (MAGL) for 2-AG), as well as the anandamide membrane transporter. Although the role of this complex neurobiological system in sleep-wake modulation has been described, the contribution of the blocker of FAAH and the transient receptor potential cation channel subfamily V member 1 (TRPV1), N-arachidonoyl-serotonin (AA-5-HT), in sleep has not been investigated. In the present study, varying doses of AA-5-HT (5, 10 or 20mg/Kg, i.p.) at the beginning of the lights-on period of rats, caused no significant changes in sleep patterns. However, a similar pharmacological treatment to animals at the beginning of the dark period induced a dose-dependent effect by decreasing wakefulness and increasing slow wave sleep (SWS) and rapid eye movement sleep (REMS). Power spectra analysis of states of vigilance during the lights-off period showed that injection of AA-5-HT diminished alpha spectrum during alertness. In opposition, delta power spectra was found enhanced as well as theta spectrum, during SWS and REMS, respectively. At highest doses, AA-5-HT decreased wake-related neurochemicals including dopamine, noradrenaline, serotonin, and epinephrine, whereas the levels of the sleep-related compound adenosine were enhanced. Lastly, AA-5-HT blocked the wake-inducing effects of either cannabidiol (30mg/Kg) or modafinil (30mg/Kg). Overall, our findings suggest that simultaneous FAAH activity and TRPV1 activation play a critical role for sleep control as well as the release of sleep-related neurochemicals, which can be therefore modulated by AA-5-HT. These data suggest that AA-5-HT might control insomnia-like behaviors.